[5-(4-Bromophenoxymethyl)-1,3,4-thiadiazole-2-thiolato]triphenyltin(IV) - Lai-jin Tian; Zhi-feng Wang; Gui-long Zhao (Acta Crystallographica Section E, 2009)
In title compound, [Sn(C6H5)3(C9H6BrN2OS2)], the Sn atom is five-coordinated and the 1,3,4-thiadiazole-2-thiol ligand acts as an S,N-bidentate chelating ligand. The five-coordinate SnIV atom forms four primary bonds, three to the phenyl groups and one to the S atom. Thus, the title complex has a distorted cis-trigonal bipyramidal geometry with the S atom and two C atoms occupying the equatorial plane, whereas the N atom and another C atom are in axial positions. In addition, there is a weak intramolecular Sn...N interaction. The crystal structure involves weak intramolecular C—H...N and intermolecular C—H...Br hydrogen bonding.